Evaluation of the Bond Strength of Universal Adhesive Systems after Application of 2% Chlorhexidine - María LLashag Bello; Marcia Edith Vidalón Pinto (Editorial Ciencias Médicas, 2024)
Introduction: The influence of chlorhexidine on the bond strength of adhesive systems is still very controversial. Objective: To determine the bond strength of two universal adhesives on dentin after application of 2% chlorhexidine at different application times. Methods: Thirty incisors were used and the vestibular surface was abraded to expose the dentin. Subsequently, they were randomly divided into six groups (n = 5). Single Bond Universal (SBU) and All-Bond Universal (ABU) adhesives with/without chlorhexidine were used. Group SBU-0: Single Bond Universal; Group SBU-30: chlorhexidine for 30 seconds + Single Bond Universal; Group SBU-60: chlorhexidine for 60 seconds + Single Bond Universal; Group ABU-0: All-Bond Universal; Group ABU-30: chlorhexidine for 30 seconds + All-Bond Universal and Group ABU-60: chlorhexidine for 60 seconds + All-Bond Universal. Adhesive strength was analyzed by two-factor mixed ANOVA and Tukey's post hoc (p < 0.05). Results: The bond strength for the SBU-60 group increased significantly with respect to the control group (p = 0.032). Similarly, for the ABU-30 and ABU-60 groups, the bond strength increased significantly with respect to the control group (p = 0.001) and (p = 0.000), respectively. Conclusion: Pre-application of 2% chlorhexidine for 60 seconds increases the bond strength of Single Bond Universal and All-Bond Universal adhesive systems.